Uncoupling Protein-2 Decreases the Lipogenic Actions of Ghrelin - Andrews, Zane B. (The Endocrine Society, 2010)
The exact mechanisms through which ghrelin promotes lipogenesis are unknown. Uncoupling protein (UCP)-2 is a mitochondrial protein important in regulating reactive oxygen species; however, recent research shows that it may play an important role fat metabolism. Given that ghrelin increases UCP2 mRNA in white adipose tissue, we examined whether the lipogenic actions of ghrelin are modulated by UCP2 using ucp2(+/+) and ucp2(−/−) mice. Chronic ghrelin treatment either via osmotic minipumps or daily ip injections induced body weight gain in both ucp2(+/+) and ucp2(−/−) mice; however, body weight gain was potentiated in ucp2(−/−) mice. Increased body weight gain was completely due to increased body fat as a result of decreased fat oxidation in ucp2(−/−) mice. Ghrelin treatment of ucp2(−/−) mice resulted in a gene expression profile favoring lipogenesis. In a calorie-restriction model of negative energy balance, ghrelin to ucp2(+/+) mice did not increase body weight; however, ghrelin to ucp2(−/−) mice still induced body weight. These results show that UCP2 plays an important role in fat metabolism by promoting fat oxidation and restricts ghrelin-induced lipogenesis.